Leadership in Action Assessing Emotional Intelligence - A Talk with Cary Cherniss - Alexander, John (Center for Creative Leadership, 2000)
Cary Cherniss has long been interested in emotional intelligence-a set of personal and interpersonal competencies that determine how people manage their feelings, interact, and communicate-and how it works in leaders.